Challenges of Efficacy Assessments in Pseudomyxoma Peritonea. (5th February 2015) - Overman, Michael J.; Eng, Cathy; Raghav, Kanwal; Matamoros, Aurelio; Taggart, Melissa; Foo, Wai Chin; Fournier, Keith
Abstract : Several critical issues need to be considered in interpreting the results of the single‐center observational study of the FOLFOX regimen in appendiceal pseudomyxoma peritonei reported by Pietrantonio et al.